Crack Evolution and Estimation of Fracture Toughness of HfO2/SiCN(O) Polymer Derived Ceramic Nanocomposites1. Issue 9 (9th February 2015) - Sujith, Ravindran; Zimmermann, Andre; Kumar, Ravi
<x xml:space="preserve">Abstract</x> In this study the crack evolution and fracture toughness of HfO2/SiCN(O) ceramic nanocomposites were studied. These ceramics crack radially under indentation in contrast to Hertzian crack in SiOC ceramics. This difference was attributed to the variance in Poisson's ratio and elastic modulus to hardness ratio. Fracture toughness by crack opening displacement and radial crack length measurement was 0.8–1.2 MPa.m1/2 and 2.5–3 MPa.m1/2, respectively. The open network forming structure resulted in the over estimation of fracture toughness value by RCL.